Development of the Babaela Game in Getting to Know the Regional Culture of Pekalongan Regency - Kartikasari, Tanti; Priyanti, Nita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research is titled "Development of the Babaela Game in Understanding the Regional Culture of Pekalongan Regency." It aims to develop traditional game-based learning media to introduce regional culture to young children at Hasyim Asyari Mesoyi Kindergarten. The Babaela game, inspired by coconut shell clogs, serves as a fun and interactive tool for teaching local Pekalongan cultural values. The Research and Development (R&D) method with a 4D model (Define, Design, Develop, and Disseminate) is applied. The Define stage identifies the need for cultural introduction through observations and interviews. The Design stage adapts the game to early childhood characteristics and learning objectives. The Develop stage involves validation by media and cultural experts, followed by revisions. Implementation is carried out in limited classes, with evaluation focusing on children's participation and cultural understanding. Results show the Babaela game effectively boosts children's motivation and understanding of local culture, including elements like Sintren dance and Pekalongan batik. Teachers also find it practical and effective in introducing cultural values. This innovative and contextual learning media can be further developed and applied in various PAUD institutions to preserve local cultural heritage from an early age.